Senario penghasilan pola pakaian di Malaysia bagi program fesyen TVET - Norulaini Mohd Ramly (Tanjong Malim, 2019)
Senario penghasilan pola pakaian di Malaysia bagi program fesyen TVET by Norulaini Mohd Ramly